Combined effects of NPK fertilizers, biochar and fulvic acid on wheat growth in sandy soil - Nouran M. Shlatout, Mohamed K. Abdelfattah, Ahmed M. Hussin, Ahmed I. Abdo (Forest Chemicals Review)
Background: Wheat production in sandy soil is affected by the losses of applied mineral fertilizers and environmental stresses. We hypothesized that combining NPK fertilizers with biochar and fulvic acid (FA) could improve wheat growth and reduce nutrients losses. Methods: We conducted a pot experiment during 2017/2018 under wheat (Triticum aestivum cv., Misr 1). Four rates of mineral fertilizers were applied including 160, 310, 475 and 635 kg ha-1 of super phosphate, 143, 190, 240 and 285 kg ha-1 of potassium sulphate and 120, 180, 240, 300 kg ha-1 of ammonium nitrate. Biochar was applied at rates 0, 15 and 30 Mg ha-1. Fulvic acid was foliar applied on wheat plants at a rate of 0.2 g L-1. Result: Our results showed that combined application of highest NPK rate with 30 Mg ha-1 biochar and FA resulted in the maximum straw and grains N, P and K contents (2.37, 0.59, 2.36, 2.88, 0.97 and 2.31%, respectively). Applying the maximum rate of NPK fertilizers, 30 Mg ha-1 of biochar and FA resulted in increasing plant height by 27% and duplicated grain yield and biological yield as compared with no amendments. In conclusion, we recommended combining NPK fertilizers with biochar and FA for optimizing wheat growth and productivity in sandy soils.